Morphological changes in the Heart in unrelated deaths (Journal of Pathology of Nepal, 2016)
Background: Cardiovascular diseases are the major cause of morbidity and mortality worldwide. In the Indian subcontinent, they account for more than 25% of deaths. Numerous studies have been conducted on the cardiovascular system in cases of sudden death; but there has been a major neglect to study the heart in cases of people who died of unrelated causes.In the present study, we have attempted to study the CVS in detail in those individuals who died of unrelated causes and have tried to assess the prevelance of atherosclerosis, conduction system lesions, inflammatory and valvular pathologies in them.Materials and Methods: The present study was a prospective one conducted from June 2007 to June 2009 in the department of Pathology, Kasturba Medical College, Mangalore. The hearts of persons who died of unrelated causes were studied.Results: Various lesions encountered in the heart were coronary artery disease (70.58%), medial hyperplasia of SAnode (38.23%) and AV node (55.88%), chronic inflammation of the conduction system (55.88%) and calcification (11.76%). Malarial myocarditis was seen in 5.88% and pulmonary stenosis was seen in 2.94% of the cases. No cardiac pathology was detected in 5.88% cases.Conclusion: Our study highlights the prevelace of atherosclerotic changes and conduction system abnormalities in the general population. Hence, we conclude that examination of the CVS is extremely important in cases of sudden death; but it should also be made mandatory in unrelated deaths too, as it can diagnose a lot of hidden pathology.